2022
DOI: 10.1007/s00784-021-04364-y
|View full text |Cite
|
Sign up to set email alerts
|

Peri-implant tissue conditions following transcrestal and lateral sinus floor elevation: 3-year results of a bi-center, randomized trial

Abstract: Objectives The present study was performed to comparatively evaluate the peri-implant bone stability and conditions of marginal tissues at 3 years following transcrestal and lateral sinus floor elevation (tSFE and lSFE, respectively). Materials and methods Patients included in a parallel-arm randomized trial comparatively evaluating tSFE and lSFE were recalled at 3 years post-surgery. Twenty-one and 24 patients in tSFE and lSFE groups, respectively, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 54 publications
0
17
0
1
Order By: Relevance
“…Details regarding the study methodology have been reported in previous articles (Farina et al, 2018, 2019; Farina, Franzini, Minenna, et al, 2023; Farina, Simonelli, Franceschetti, Minenna, et al, 2022; Farina, Simonelli, Franceschetti, Travaglini, et al, 2022). Briefly, patients contributing one edentulous maxillary posterior site with a residual bone height of 3–6 mm were randomly assigned to receive tSFE or lSFE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details regarding the study methodology have been reported in previous articles (Farina et al, 2018, 2019; Farina, Franzini, Minenna, et al, 2023; Farina, Simonelli, Franceschetti, Minenna, et al, 2022; Farina, Simonelli, Franceschetti, Travaglini, et al, 2022). Briefly, patients contributing one edentulous maxillary posterior site with a residual bone height of 3–6 mm were randomly assigned to receive tSFE or lSFE.…”
Section: Methodsmentioning
confidence: 99%
“…Several randomized or quasi‐randomized trials have been conducted comparing tSFE and lSFE for chair time (Bacevic et al, 2021; Farina et al, 2018), morbidity (Al‐Almaie et al, 2017; Bacevic et al, 2021; Bensaha, 2011; Cannizzaro et al, 2009; Farina et al, 2018; Temmerman et al, 2017;Yu et al, 2017; Zhou et al, 2021), radiographic outcomes (Al‐Almaie et al, 2017; Bacevic et al, 2021; Bensaha, 2011; Cannizzaro et al, 2009; Farina et al, 2019; Temmerman et al, 2017; Yu et al, 2017; Zhou et al, 2021), surgery‐related costs and specific aspects of oral health‐related quality of life (Farina, Simonelli, Franceschetti, Travaglini, et al, 2022). Follow‐up data from comparative randomized studies, however, remains limited to a few trials with a follow‐up of 2 (Yu et al, 2017; Zhou et al, 2021), 3 (Al‐Almaie et al, 2017; Farina, Simonelli, Franceschetti, Minenna, et al, 2022) or 5 years (Cannizzaro et al, 2013), the majority of which refers to different surgical conditions between treatments (Al‐Almaie et al, 2017; Cannizzaro et al, 2013; Yu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Two surgical procedures for SFE have been known: the lateral window technique and the crestal osteotome technique [1]. The previous studies reported that both techniques were clinically reliable due to high success rates of implants after SFE [3][4][5][6]. However, there are some considerations to decide surgical procedures such as the preexisting bone height between sinus floor and maxillary bone crest, and the timing of implant placement [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] Based on moderate-quality evidence, a network meta-analysis showed that transcrestal sinus floor elevation is superior to lateral sinus floor elevation at sites with a residual bone height of 4-8 mm. 30 A recent randomized trial conducted a comparative evaluation of transcrestal sinus floor elevation (performed according to a standardized sequence of manual and rotating instruments used with stop devices) and lateral sinus floor elevation at sites with a residual bone height of 3-6 mm, generating data on morbidity, 31,32 radiographic outcomes, 32,33 chair time, 31 costs, 34 and specific aspects of oral health-related quality of life. 34 Several results favored transcrestal sinus floor elevation (Table 1).…”
mentioning
confidence: 99%
“…34 Several results favored transcrestal sinus floor elevation (Table 1). When considered collectively, the meta-analysis by Al-Moraissi et al 30 and the clinical trial by Farina and coworkers [31][32][33][34] clearly indicate that one of the aspects supporting the use of transcrestal sinus floor elevation resides in its limited invasiveness. Within the context of sinus floor elevation procedures, "invasiveness" is a broad term that includes need/number of invasive preoperative diagnostic examinations; intra-and postoperative morbidity, complications, and adverse events with respect to the surgical protocol; number of surgical sessions and chair time needed for each session; need for autologous tissue harvesting and/or reconstructive devices; and costs related to the surgery (eg, anesthetic, graft material) and postsurgery phases (eg, management of complications).…”
mentioning
confidence: 99%